The Effectiveness of Positive Thinking Skills on Guilt Feelings, Rumination, and Hope for Life in the Elderly - Mohammadpour, Mansoureh; Esmaeilnia Ghara, Mohammadreza (Mental Health and Lifestyle Journal, 2026)
ABSTRACT The present study aimed to examine the effectiveness of positive thinking skills on guilt feelings, rumination, and hope for life among elderly individuals in the city of Qaemshahr. Based on its objective, the study is applied in nature. The research design was quasi-experimental, employing a pretest–posttest format with a control group. The statistical population included all elderly residents of Qaemshahr who were living in nursing homes. A total of 30 participants were selected and randomly assigned to experimental and control groups; to control for group effects, both groups were selected from the same nursing home. Data were collected using the Snyder Hope Scale (Snyder, 1991), the Ruminative Responses Scale developed by Nolen-Hoeksema and Morrow (Nolen-Hoeksema & Morrow, 1991), and the Guilt Inventory by Kugler and Jones (Kugler & Jones, 1992) at two stages, pretest and posttest. The intervention consisted of the Susan Quilliam protocol, translated by Barati and Sadeghi (2011), along with the book The Optimistic Child by Martin Seligman et al., translated by Davarpanah (2012), administered over 10 sessions of 90 minutes each across 10 weeks. Data were analyzed using univariate and multivariate analysis of covariance (ANCOVA and MANCOVA). The results indicated that positive thinking skills had a significant effect on guilt feelings, rumination, and hope for life. The largest effect size was observed for hope for life (55%), followed by guilt feelings (approximately 44%), and rumination (35%). Based on the findings, the implementation of positive thinking training programs appears necessary for reducing rumination and guilt while enhancing hope for life among the elderly.